Heuristics for NP-hard optimization problems - Žerovnik, Janez (Logistics and sustainable transport, 2015)
We provide several examples showing that local search, the most basic metaheuristics, may be a very competitive choice for solving computationally hard optimization problems. In addition, generation of starting solutions by greedy heuristics should be at least considered as one of very natural possibilities. In this critical survey, selected examples discussed include the traveling salesman, the resource-constrained project scheduling, the channel assignment, and computation of bounds for the Shannon capacity.
Keywords: greedy construction; konstrukcijska hevristika; local search; lokalno iskanje; metaheuristics; metahevristika; optimizacija; optimization; požrešna metoda; problem trgovskega potnika; traveling salesman problem